DO OBEDIENCE PRESSURE AND TASK COMPLEXITY AFFECT AUDIT DECISION? - Cahyaningrum, Christina Dwi; Utami, Intiyas (UI Scholars Hub, 2015)
Pressures from various parties may impact auditor’s decisions. Complex and interrelated tasks can also inhibit auditor to search for relevant information, to process it, and to determine audit decision. This study aims to investigate the accuracy of audit decision made by junior auditors when they face obedience pressure and task complexity. Using accounting bachelor students as surrogates of junior auditors, we conduct a 2x2x2 between-subject experimental design to test our hypotheses. We manipulate both obedience pressure and task complexity into high and low condition. The results show that participants who receive both low obedience pressure treatment and low task complexity treatment make more accurate audit decision. It is expected that our research could inform practitioners the importance of minimizing the side effect of obedience pressure and task complexity on inaccurate audit decision.